Immunometabolic control of hematopoiesis - Hajishengallis, George (Mol Aspects Med, 2020)
Hematopoietic stem cells (HSC) lie at the center of the hematopoiesis process, as they bear capacity to self-renew and generate all hematopoietic lineages, hence, all mature blood cells. The ability of HSCs to recognize systemic infection or inflammation or other forms of peripheral stress, such as blood loss, is essential for demand-adapted hematopoiesis. Also of critical importance for HSC function, specific metabolic cues (e.g., associated with changes in energy or O(2) levels) can regulate HSC function and fate decisions. In this regard, the metabolic adaptation of HSCs facilitates their switching between different states, namely quiescence, self-renewal, and proliferation, differentiation. Specific metabolic alterations in hematopoietic stem and progenitor cells (HSPCs) have been linked with the induction of trained myelopoiesis in the bone marrow as well as with HSPC dysfunction in aging and clonal hematopoiesis of indeterminate potential (CHIP). Thus, HSPC function is regulated by both immunologic/inflammatory and metabolic cues. The immunometabolic control of HSPCs and of hematopoiesis is discussed in this review along with the translational implications thereof, that is, how metabolic pathways can be therapeutically manipulated to prevent or reverse HSPC dysfunction or to enhance or attenuate trained myelopoiesis according to the needs of the host.